Unraveling the Oxygen‐Reduction Sites in Graphitic‐Carbon Co–N–C‐Type Electrocatalysts Prepared by Single‐Precursor Pyrolysis. Issue 11 (3rd May 2017) - Subramanian, Palaniappan; Mohan, Roopathy; Schechter, Alex
Abstract: Metal‐ and nitrogen‐doped carbon‐based hybrid materials (M–N–C) are widely regarded as promising alternative to platinum for catalyzing the oxygen‐reduction reaction (ORR) in fuel‐cell cathodes. The two important steps involved in the preparation of these catalysts are acid washing and a second heat treatment of the pyrolyzed mixture made of carbon, nitrogen, and metal precursors (M). We have explored in detail the changes induced by the post‐treatment steps on structure, composition, and oxygen‐reduction activity of new hybrid catalysts prepared by the prolonged pyrolysis of a single well‐defined organometallic precursor. The marginal increase in nitrogen content, apparent BET surface area, porosity, surface defects, and the higher degree of graphitization positively contribute to the substantial improvement in ORR activity of post‐treated catalysts in alkaline solution, whereas this procedure is found to have a weaker influence on the ORR activity in acid solution. The findings from this study suggest that both free and nitrogen‐coordinated metal sites, specifically, "Co2 N" sites, which are present in the catalyst bulk and protected by the nitrogen‐doped graphitic carbon layer, are most likely the active sites in Co–N–C catalysts. Based on these experimental results, we propose a model that will assist in improving the understanding of plausible functioning of these active sites in acid and alkaline solution. Abstract : Protected active sites : Co2 N nanoparticles evolved after post‐treatment steps improve the oxygen‐reduction activity both in alkaline and acid solution. The confinement of metallic and Co2 N particles within graphitic carbon sheets protects the particles from leaching in acidic solution, but protonation slows down oxygen reduction.